Evaluation of the Uncertainty of Surface Temperature Measurements in Photovoltaic Modules in Outdoor Operation - Carmen García-López; Germán Álvarez-Tey (Sensors, 2022)
Faults in photovoltaic modules in operation can lead to power losses. By determining the module surface temperature, hot spots that can potentially cause this power loss can be detected. Temperature measurement by radiation allows a complete, reliable, and fast qualitative determination of hot spots on PV modules in outdoor operation. However, to obtain quantitative values, it is necessary to consider multiple factors: emissivity, reflected radiation, wind speed, intensity, shading, etc. Temperature quantitative measurement evaluation by contact is more studied, although by this technique it is impossible to examine the temperature of the entire module to detect hot spots because it is a point measurement and due to shading caused by the measurement probe on the surface. In this work, a method of temperature measurement by radiation is described, evaluating the uncertainty components, and a comparison is made with temperature measurement by contact on the module rear side points where module heating has been detected, also evaluating the uncertainty components. This comparison of both methods and uncertainty determination allows establishing a methodology in quantitative temperature measurement by radiation in photovoltaic modules in outdoor operation.